SAFETY AND RISK ANALYSIS OF A BANKING FACILITY - Paweł Sitek (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2016)
From the objective point of view, safety of a banking facility is nothing more than organized opposition against any threats caused by human actions, force of nature as well as shortcomings in the civilization and threats in the bank continuity as a whole and individual elements of its material and non-material structure. The basic determinant of such approach is to maintain management continuity of a bank facility at any time and in any circumstances of its operation. The basis for that is the shape and quality of legal and organizational solutions as well as reliable and substantive assessment of the security risks of a bank facility including all the aspects of these threats. The main purpose of the research was to make a theoretical assessment of a bank facility safety in terms of potential threats.